Metalorganic Chemical Vapor Deposition Approach to the Synthesis of Perovskite BaCeO3 and BaCe0.8Y0.2O3 Thin Films - Anna L. Pellegrino; Francesca Lo Presti; Graziella Malandrino (Molecules, 2023)
In the present energetic scenario, the development of materials with high potentiality in the technological fields of energy conversion processes, production and storage of hydrogen, are of great interest in the scientific community. In particular, we report for the first time the fabrication of crystalline and homogeneous barium-cerate-based materials in the form of thin films on various substrates. Starting from the β-diketonate precursor sources Ce(hfa)3diglyme, Ba(hfa)2tetraglyme and Y(hfa)3diglyme (Hhfa = 1,1,1,5,5,5-hexafluoroacetylacetone; diglyme = bis(2-methoxyethyl)ether; tetraglyme = 2,5,8,11,14-pentaoxapentadecane), a metalorganic chemical vapor deposition (MOCVD) approach has been successfully applied to the fabrication of BaCeO3 and doped BaCe0.8Y0.2O3 systems in the form of thin films. Structural, morphological and compositional analyses allowed for an accurate determination of the properties of deposited layers. The present approach represents a simple, easily scalable, and industrially appealing process for the production of compact and homogeneous barium cerate thin films.